Reseña de D. Charpin (2022), En quête de Ninive. Des savants français à la découverte de la Mésopotamie, Paris: Collège de France – Les belles lettres, 464 págs. ISBN: 978-2-251-45358-3 - Álvarez García, Juan (Panta Rei. Revista digital de Historia y Didáctica de la Historia, 2024)
The purpose of this review is to present the latest work by Dominique Charpin, professor at the Collège de France and head of the chair of Mesopotamian Civilisation, in which he develops a history of French Assyriology from 1842, when the excavations of P. E. Botta began in Khorsabad, to 1975, when D. Charpin himself joined the discipline of Assyriology.